Interactive whiteboard as a teaching aid - Ismail, Nor Zalina; Razak, Mohd Rizal; Razali, Azlini; Othman, Mahfudzah (2009)
The teaching and learning process based on resources is a topic that has always been emphasized by educators all over the world. The changes in education aids are influenced by the changes in technology. Nowadays, educators not only rely on white board and markers as a medium for teaching and learning process, but also on Overhead Projector (OHP), computers, document cameras and the latest, the Interactive Whiteboards. The Interactive Whiteboard is used all over the world as an important tool for the teaching and learning process. An interactive whiteboard is used for teaching and learning process in educational activities and also for presentations and discussions in business. There are a lot of electronic tools provided by the Interactive Whiteboards such as digital ink, digital eraser and touch screen. These features give a lot of benefits to the educators and learners such as increase the learners' interest, understanding and motivation level.